Bioinspired metal complexes for energy-related photocatalytic small molecule transformation. Issue 99 (10th December 2020) - Wu, Hao-Lin; Li, Xu-Bing; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : This article features the recent progress of bioinspired metal complexes as catalysts with high stability, specific selectivity and satisfactory efficiency to drive multiple-electron and multiple-proton related to small molecule transformation. Abstract : Bioinspired transformation of small-molecules to energy-related feedstocks is an attractive research area to overcome both the environmental issues and the depletion of fossil fuels. The highly effective metalloenzymes in nature provide blueprints for the utilization of bioinspired metal complexes for artificial photosynthesis. Through simpler structural and functional mimics, the representative herein is the pivotal development of several critical small molecule conversions catalyzed by metal complexes, e.g., water oxidation, proton and CO2 reduction and organic chemical transformation of small molecules. Of great achievement is the establishment of bioinspired metal complexes as catalysts with high stability, specific selectivity and satisfactory efficiency to drive the multiple-electron and multiple-proton processes related to small molecule transformation. Also, potential opportunities and challenges for future development in these appealing areas are highlighted.